Impacts of Land Surface Conditions and Land Use on Dust Events in the Inner Mongolian Grasslands, China - Yong, Mei; Shinoda, Masato; Nandintsetseg, Banzragch; Bi, Lige; Gao, Hailin; Wang, Yingshun (Frontiers in Ecology and Evolution, 2021)
Aeolian processes in temperate grasslands (TGs) are unique because the plant growth–decay cycle, soil water, and land-use interactions affect the seasonal and inter-annual changes in dust events. Land use types in Inner Mongolian TGs are unique (settled grazing and grass mowing) compared to those in Mongolian TGs. Since 2003, land use has been controlled by grassland protection legislation, which is intended to prevent desertification and dust storms. In this study, we used process-based ecosystem (DAYCENT) and statistical modeling, along with dust event observations from March to June of 1981–2015, to (1) identify critical land surface factors controlling dust emissions (vegetation components; live grass, standing dead grass, and litter and soil moisture ) at typical and desert steppe sites in Inner Mongolia and (2) estimate the impact of controlled land-use legislation on dust events. The DAYCENT model realistically simulated the dynamics of the observed vegetation components and soil moisture in 2005–2015. At both sites, similar significant correlations were obtained between spring dust events and wind speed, or a combination of all surface factors that retained anomalies (memory) from the preceding year. Among the surface factors, vegetation was a critical factor that suppress dust in Inner Mongolian TGs, similar to Mongolian TGs. In the desert steppe, standing dead grass had the strongest memory and was significantly correlated with dust events, while no significant correlations was observed in the typical steppe. This suggests that, in a typical steppe region, intense grazing and mowing results in less dead grass, thereby inhibiting the prevention of dust events. Moreover, the simulations of dust events under controlled (light grazing) and uncontrolled (heavy grazing) land-use conditions indicate that, the grassland protection legislation has reduced the occurrence of dust events in typical and desert steppe sites by 25% and 40%, respectively, since 2003.